TINJAUAN KRITIS DAN MENYELURUH TERHADAP FUNDAMENTALISME DAN RADIKALISME ISLAM MASA KINI - Ahdar Ahdar (LPPM IAIN Parepare, 2017)
The purpose of this research is to present a historical review and critique of the actions of radicalism on the basis of fundamentalism in Indonesia. This research is motivated by the development of discourse related to fundamentalism and radicalism which is often identified to Islam group with negative connotation in Indonesia. The methodology used in this research is a qualitative descriptive approach with a historical-critical study method. Data were collected through literature studies and related literature of several Islamic organizations consisting of; Darul Islam Or Islamic State of Indonesia (NII); Majelis Mujahidin Indonesia (MMI); Hizbut Tahrir Indonesia (HTI); and the Islamic Defenders Front (FPI). The results show that fundamentalism and radicalism is a verbic word whose roots are not contained in the language of Muslims in various Arabic speaking countries. Fundamentalism by term is the assertion of certain religious activists who define religion absolutely and literally. Fundamentalism as a reaction to modernism emerged in the nineteenth century. At that time, modernism appeared very fiery in the United States. In the era of the 1990s, there was a change of format and fundamental strategy in radical Islamic movement in Indonesia. If in previous years this movement runs latently and always confronted by the State so as to generate political fear for Muslims then in the era of the 1990s radical Islamic movement appears openly, as seen in the movement Laskar Jihad, Jamaah Islamiah Ahlussunnah wal Jamaah, Ikhwanul Muslimin, Mujahidin Jamaah, Nurul Fikr, Islamic Defenders Front and Hizb ut-Tahrir Based on the results of research, author concluded that Fundamentalism and radicalism is not a term derived from Islam but the term of Christianity which is today used for Islam. Both fundamentalism and radicalism potentially exist to any group, whether religious, social, or political. It occurs in any religion. Fundamentalism can be a virtue if it is not performed by the action of radicalism. Therefore, the solution to the value of tolerance in fundamentalism is a deep understanding of belief or religion.